Envelhecimento, experiência e competência : uma abordagem ergonômica - Nunes, Gabriela Salomé (Universidade Federal de São Carlos, 2015)
The study of the relationship between aging, experience and competence has gained great attention because of the paradox faced by industries related to age and knowledge of its workers. You can see inexperienced young people with high-level training as opposed entering the labor market for older workers with less education, however with more experience. It is known that the aging labor situation puts physical and psychological changes resulting from advancing age, but also causes the increase of experience, which enables to accelerate and enrich the production process generating evolution of workers' skills. Several studies have been conducted principally aiming to understand the relationship between aging and work, however, most of these aging studies only in extreme ages beyond, focusing on losses resulting from the process instead of positives. Thus, in order to understand how the regulation is among the factors related to aging and gain experience as well as the development of skills of operators within a structural assembly sector, was held a review of the literature followed a study case in an industrial sector of aircraft assembly. Participants were five operators of different ages and working time. The data was collected by conducting interviews within the productive sector, followed by Work Ability Index questionnaire and perform the analysis of the activity. The data collected allowed the observation that the benefits arising from the gain experience and acquire skills stand out relative declines caused by chronological aging. Furthermore, it was observed that learners operators use a longer time to complete their activities, prioritized performance of the task on time at the expense of health protection and presenting a more detailed and preformed action sequence. It was also observed that the interaction between experienced operators and apprentices is critical for the exchange of knowledge in occupational environment. Thus, the study contributes to the understanding of the relationship between aging, experience and expertise focusing on the positive aspects that permeate this relationship.
Keywords: Envelhecimento; Competência; Experiência; Análise do trabalho; Aging; Competence; Experience; Work; Activity analysis; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO